2003
DOI: 10.1159/000075206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Arterial Endothelin-1 Levels, before and during a Sleep Study, in Patients with Bronchial Asthma and Chronic Obstructive Pulmonary Disease

Abstract: Background: Endothelin (ET)-1 has been implicated in the pathogenesis of asthma and chronic obstructive pulmonary disease (COPD). The ET-1 levels are elevated during exacerbations of asthma and COPD in bronchoalveolar lavage, serum, and sputum, falling with treatment of the exacerbations. Objective: The aim of this study was to examine the ET-1 blood levels in stable asthmatic patients and stable COPD patients during alertness and sleep. Materials and Methods: We examined 48 COPD and 20 asthmatic patients. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
8
2
Order By: Relevance
“…In blood, BALF or sputum, ET1 concentration has been shown to be either normal 17,33 or increased. [33][34][35][36][37] In the present study, no significant difference in serum ET1 concentration was found between dogs with CB and healthy dogs, although high concentrations were found in 2 animals with CB. The reason why some individuals in the CB group had increased serum ET1 concentrations is unknown, but is not related to features such as duration of clinical signs.…”
Section: Discussioncontrasting
confidence: 56%
“…In blood, BALF or sputum, ET1 concentration has been shown to be either normal 17,33 or increased. [33][34][35][36][37] In the present study, no significant difference in serum ET1 concentration was found between dogs with CB and healthy dogs, although high concentrations were found in 2 animals with CB. The reason why some individuals in the CB group had increased serum ET1 concentrations is unknown, but is not related to features such as duration of clinical signs.…”
Section: Discussioncontrasting
confidence: 56%
“…Cigarette smoking is associated with increased levels of ET-1, which has been implicated in the pathogenesis of COPD, asthma and PH (Hay, 1999;Nikolaou et al, 2003). It is estimated that more than 80% patients with COPD have been cigarette smokers ) and that more than 50% of smokers have evidence of COPD (Lundback et al, 2003) .…”
Section: Evaluation Of Current Knowledge and Proposals For New Ideas mentioning
confidence: 99%
“…ET-1 is implicated in the regulation of regional blood flow and maintenance of vascular tone (84). ET-1 plays an important role in the pathogenesis of various diseases, including myocardial infarction (112), bronchial asthma (113), pulmonary hypertension (114), renal failure (115), and sepsis (13). Sharma et al (13), have demonstrated elevated plasma and myocardial ET-1 levels at 4, 8, 12-h post-sepsis induction that returned to baseline values 24-h later ( Figure 6).…”
Section: Et-1 and Sepsis-induced Myocardial Dysfunctionmentioning
confidence: 99%